Development of Gluten-Free Bread Using Cassava and Sorghum Flour Blends - Oluwakemisola, Daramola Precious (Darul Yasin Al Sys, 2025)
Cassava–sorghum flour blends have garnered growing interest in gluten-free bread production due to their complementary functional and nutritional attributes. This review synthesizes findings from peer-reviewed literature on the synergistic effects of these blends in enhancing bread texture, flavor, and nutritional quality, with a focus on optimal blending ratios, loaf volume, crumb softness, and shelf life. Evidence indicates that incorporating approximately 25% sorghum flour into cassava-based formulations preserves favorable sensory properties while improving dietary fiber content, antioxidant capacity, and glycemic control relative to traditional wheat-based breads. While cassava contributes advantageous starch characteristics, its inherently low protein and micronutrient content necessitates targeted fortification strategies, including the addition of proteins, vitamins, and minerals. Notable research gaps include limited studies on long-term shelf life, the efficacy of nutrient fortification, and challenges in scaling up production. Emerging food technologies, such as enzyme application, extrusion, and hydrocolloid incorporation present promising opportunities for optimizing product quality and functional performance. Overall, cassava–sorghum breads offer substantial potential in expanding the gluten-free product market, particularly when formulation and processing methods are strategically refined to meet both nutritional and sensory expectations.